Economic Analysis of Improved Alkaline Water Electrolysis - Kuckshinrichs, Wilhelm; Ketelaer, Thomas; Koj, Jan Christian (Frontiers in Energy Research, 2017)
Alkaline water electrolysis (AWE) is a mature hydrogen production technology and there exists a range of economic assessments for available technologies. For advanced AWEs, which may be based on novel polymer-based membrane concepts, it is of prime importance that development comes along with new configurations and technical and economic key process parameters for AWE that might be of interest for further economic assessments. This paper presents an advanced AWE technology referring to three different sites in Europe (Germany, Austria, and Spain). The focus is on financial metrics, the projection of key performance parameters of advanced AWEs, and further financial and tax parameters. For financial analysis from an investor’s (business) perspective, a comprehensive assessment of a technology not only comprises cost analysis but also further financial analysis quantifying attractiveness and supply/market flexibility. Therefore, based on cash flow (CF) analysis, a comprehensible set of metrics may comprise levelised cost of energy or, respectively, levelized cost of hydrogen (LCH) for cost assessment, net present value (NPV) for attractiveness analysis, and variable cost (VC) for analysis of market flexibility. The German AWE site turns out to perform best in all three financial metrics (LCH, NPV, and VC). Though there are slight differences in investment cost and operation and maintenance cost projections for the three sites, the major cost impact is due to the electricity cost. Although investment cost is slightly lower and labor cost is significantly lower in Spain, the difference can not outweigh the higher electricity cost compared to Germany. Given the assumption that the electrolysis operators are customers directly and actively participating in power markets, and based on the regulatory framework in the three countries, in this special case electricity cost in Germany is lowest. However, as electricity cost is profoundly influenced by political decisions as well as the implementation of economic instruments for transforming electricity systems toward sustainability, it is hardly possible to further improve electricity price forecasts.